Development of a functional near-infrared spectroscopy based objective measure of paediatric cochlear implant outcome - Mushtaq, F. (2020)
A cochlear implant (CI) is a surgically implanted prosthetic device that is used to partially restore the sensation of hearing in deaf individuals. In the United Kingdom, CIs are the therapy of choice for profoundly deaf children. In the case of congenital deafness, CIs are often fitted within the first year of life in order to facilitate spoken language acquisition. However, although most children develop good speech skills, outcomes remain varied.